2008
DOI: 10.1016/j.brainresbull.2007.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulotrigeminal pathways in the frog, Rana esculenta

Abstract: The aim of this study was to investigate whether primary vestibular afferent fibers establish direct connections with the motor and sensory trigeminal system in the brainstem of the frog. The experiments were carried out on Rana esculenta. In anaesthetized animals the trigeminal and vestibular nerves were prepared, and their proximal stumps were labeled either with fluorescein binding dextran amine (trigeminal nerve) or tetramethylrhodamine dextran amine (vestibulocochlear nerve). With a confocal laser scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(4 reference statements)
0
2
0
1
Order By: Relevance
“…5 summarizes the present and previous data concerning the direct and indirect sensory input to the brainstem networks of preycatching behavior in the frog (Anderson, 2001;Antal et al, 1980;Corbacho et al, 2005;Deak et al, 2009;Harwood and Anderson, 2000;Kecskes et al, 2013Kecskes et al, , 2015Mandal and Anderson, 2010;Matesz, 1994;Matesz et al, 2008Matesz et al, , 2014Nishikawa, 2000). We can hypothesize that direct contacts of the trigeminal fibers with the trigeminal and facial motoneurons can be the morphological background of the synchronization and timing of the jaw closing and opening during the feeding movements.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…5 summarizes the present and previous data concerning the direct and indirect sensory input to the brainstem networks of preycatching behavior in the frog (Anderson, 2001;Antal et al, 1980;Corbacho et al, 2005;Deak et al, 2009;Harwood and Anderson, 2000;Kecskes et al, 2013Kecskes et al, , 2015Mandal and Anderson, 2010;Matesz, 1994;Matesz et al, 2008Matesz et al, , 2014Nishikawa, 2000). We can hypothesize that direct contacts of the trigeminal fibers with the trigeminal and facial motoneurons can be the morphological background of the synchronization and timing of the jaw closing and opening during the feeding movements.…”
Section: Resultsmentioning
confidence: 85%
“…Several studies (Anderson, 2001;Corbacho et al, 2005;Mandal and Anderson, 2010;Matsushima et al, 1986;Nishikawa, 2000) suggested polysynaptic pathways between sensory fibers and motoneurons involved in the prey catching behavior. Although the possible influence of the primary afferents on the activity of jaw opening muscle is not yet determined, direct contacts have been verified between sensory fibers and various motoneurons supplying jaw closing and tongue muscles as well as those involved in swallowing (Deak et al, 2009;Kecskes et al, 2013Kecskes et al, , 2015Matesz et al, 2008). The jaw opening is executed by the contraction of depressor mandibulae muscle (DMm) under the control of the facial nerve (Gans and Gorniak, 1982;Gaupp, 1904).…”
Section: Introductionmentioning
confidence: 99%
“…У низших позвоночных вестибулярные волокна составляют основной источник афферентов к аурикулярной области коры мозжечка. Известно, что нейроны МРФ амфибии обильно снабжаются вестибулярными волокнами [4]. Вестибулярные афференты влияют на нейроны МРФ также через интернейроны, локализованные в ВЯК [2].…”
unclassified